FEELING BLUE WITH YOU: AGING COUPLES' REACTIVITY TO UPSETTING PERSONAL MEMORIES AND MARITAL CONFLICT. (20th December 2022) - Wilson, Stephanie; Shrout, M Rosie; Kiecolt-Glaser, Janice K
Abstract: Reactivity to marital conflict has long been considered a critical mechanism linking marriage to health and well-being. Yet, developmental theories suggest conflict may subside with age. To compare mood and cardiovascular responses to two novel contexts—both partners' upsetting personal experiences—with marital conflict reactivity, 107 couples ages 40-87 recounted a difficult personal memory to the partner, discussed a marital problem, and provided baseline and post-task mood, blood pressure (BP), and heart rate (HR). Although older adults relived their upsetting personal memories with less emotional intensity, negative mood and systolic BP increased most after this task. Compared to disagreement, the spouse's upsetting memory triggered larger increases in negative mood, HR, and among older adults, SBP. Results suggest that both partners' upsetting personal experiences are as relevant for mood and cardiovascular activity as marital conflict in aging couples, and that spousal distress may grow increasingly important with older age.